Pengaruh Latar Belakang Pendidikan Terhadap Hambatan Pembelajaran Bahasa Arab Mahasiswa Prodi Pendidikan Bahasa Arab Di Universitas Pendidikan Indonesia Angkatan 2022 - Ghani Ahmad Haidar; Ahmad Fauzi Ismail; Sahira Asalamah; Hasna Luthfiyah Nazhif; Melza Zahra Permata; Ahmad Fu’adin (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
In general, in Indonesia Arabic is a foreign language to learn. The different educational backgrounds of students of the Arabic Language Education study program at Universitas Pendidikan Indonesia affect the level of obstacles in the process of learning and understanding Arabic. With different backgrounds, the obstacles faced by each student of Arabic Language Education also vary. Some of them who come from Islamic boarding schools and Madrasah Aliyah are accustomed to learning and practicing Arabic, so that some who come from public schools will feel left behind and have to catch up. This study aims to describe the barriers faced by Arabic Language Education students at Universitas Pendidikan Indonesia in learning Arabic with different educational backgrounds. This research uses descriptive qualitative methods. The sources taken in this study were Arabic Language Education students at Universitas Pendidikan Indonesia class of 2022.